Home Health Care for California's Injured Workers - Wynn, Barbara O.; Boustead, Anne (RAND Corporation, 2023)
The California Department of Industrial Relations/Division of Worker’s Compensation asked RAND to help develop a fee schedule for home health services provided to injured workers. After consulting stakeholders, reviewing other payers’ fee schedules, and interviewing WC administrators from other states, the researchers focused on options to create a single fee schedule covering the full range of services and made three sets of recommendations.